Intra-uterine Growth Retardation and Development of Hypertension - Haerani Rasyid; Syakib Bakri (Acta Medica Indonesiana)
Low birth weight (LBW) is defined as a birth weight of a liveborn infant of <2,500 gram. In developed countries, LBW is commonly caused by preterm birth; while in developing countries, it is mostly due to intrauterine growth retardation. The concept of developmental origins of adult diseases, particularly on late-onset diseases such as hypertension and kidney disease, implies that there is a correlation between intrauterine milieu, intrauterine growth retardation, premature birth and infant feeding. The ‘fetal origin hypothesis’ suggests that metabolic diseases are directly related to poor nutritional status in early life. There is an inverse association between LBW and later risk of hypertension. The pathomechanism that links LBW and hypertension is multifactorial including delayed nephrogenesis, genetic factors, sympathetic hyperactivity, endothel dysfunction, elastin deficiencies, insulin resistance and activation of renin-angiotension system.